Complete Replacement of Nitrite With a Lactobacillus fermentum on the Quality and Safety of Chinese Fermented Sausages - Xu, Yuning; Zhu, Yinglian (Frontiers in Microbiology, 2021)
This study investigated the positive effects of complete replacement of nitrite with a Lactobacillus fermentum on the quality and safety of Chinese fermented sausages, and evaluated the risk of this strain. The effects of the strain on pH, color, nitrite, thiobarbituric acid reactive substances (TBARS), total volatile basenitrogen (TVB-N) , metmyoglobin (Met-Mb), biological amines, free amino acid content and sensory index have been studied. The results revealed that the strain reduced the pH of the sausages, which reduced the risk of food borne pathogens, and accelerated the acidification and gelation process. The inoculation of the strain produced pink color similar to 50 mg/kg nitrite, significantly reducing the residual risk of nitrite in the sausages. In addition, the strain effectively improved quality and nutrition of the sausages through preventing fat oxidation, protein decomposition, myoglobin oxidation and increasing free amino acids content. The harmful biogenic amines species of the treated sample were reduced, though the tyramine contents were higher than the control, the contents of the two groups were all far below the specified limit (800 mg/kg). The sensory analysis showed that the strain enhanced the taste, flavour, sour and overall acceptability of the sample sausages. Therefore, replacing nitrite completely with the strain L. fermentum could be a potential strategy to produce healthier and safer acceptable sausages through decreasing the risk of nitrite, and improving nutrion and qulity of the sausages.